Analytical validation of novel consequent pole E‐core stator permanent magnet flux switching machine. Issue 5 (17th April 2020) - Ullah, Wasiq; Khan, Faisal; Sulaiman, Erwan; Umair, Muhammad; Ullah, Noman; Khan, Bakhtiar
Abstract : Flux switching machines (FSMs) encompass unique features of conventional direct current machine, permanent magnet (PM) synchronous machine and switch reluctance machine. Permanent magnet FSM (PMFSM) is capable of high torque density and applicable for high‐speed application, however conventional PMFSM exhibits demerits of high PM volume, high torque ripples and significant stator flux leakage. In this paper, a novel consequent pole E‐core stator PMFSM is proposed and compared with conventional topology utilising 2D finite‐element analysis (2D‐FEA). Finite‐element analysis revealed that proposed design enhanced flux modulation effects by introducing flux bridges and flux barriers as a result reduced cogging torque by reducing 46.53% of the total PM volume, reduce torque ripples by reducing PM slot effects and reduce flux leakage utilising flux bridges in the stator. Furthermore, analytical model for flux linkages, cogging torque, mechanical torque, no load and on‐load magnetic flux density (MFD) is developed for initial design of conventional and proposed model. 2D analytical methodologies resolve equivalent magnetic circuits for open‐circuit flux linkages, Fourier analysis for cogging torque, Laplace equations for MFD and Maxwell stress tensor for mechanical torque. Finally, results obtained from 2D‐FEA and analytical methodologies are validated and compared.